UJI TEKNIS ALAT TANAM JAGUNG (Zea mays L.) TIPE TP CSM 15 DENGAN MENGGUNAKAN TRAKTOR TANGAN SEBAGAI ALAT PENARIK1) - Idhansyah .; Ruland A Rantung; Daniel P. M Ludong (COCOS, 2018)
ABSTRACT      This study aims to test technically the corn seeds planter (Zea mays L.) type TP CSM (Corn seeding machine) 15 using the hand tractor as a pulling device on the plot of the land 30 m x 10 m. The test results of TP CSM 15 corn seeds planter in 30 m x 10 m plot of the land on 3 field tests with soil treatment got the average effective field capacity of 0,30 ha/hour, the average theoretical field efficiency of 0,47 ha/hour, and the average field efficiency of 64,20 %. The average distance between planting rows is 73,2 cm and the average distance in row planting is 28,4 cm. The number of seeds per planting hole 1 – 3 with an average of 1 seed per planting hole and an average planting depth of 5.5 cm. The percentage of seeds which grew successfully by an average of 75,74% and the percentage of seeds which unsuccessfully to grow by an average of 24,26%. Keywords : TP CSM 15, Hand Tractor, Field Efficiency.